The environmental dictionary : and regulatory cross-reference (New York : John Wiley, 1995)
Environment Management
Keywords: Dictionaries; Environment-Dictionaries; Environmental law-Dictionaries; Environmental protection-Dictionaries; Pollution-Dictionaries